An Analysis of The Relationship Between Home Environment And Emotional Intelligence of Secondary School Students (International Journal of Food and Nutritional Sciences, 2022)
Home is the place where a child feel secure after his birth. Home or family takes care of the child and provides all the support for his well-being. Child’s emotion is taking growth with the environment that is perceived by him or her. The objective of the present study is to find out the relationship between home environment and emotional intelligence of Secondary School Students. The sample of the study were selected with the help of stratified random sampling method. Total 200 sample were selected for the study. (100 male and 100 female). The results of the study revealed that home environment is significantly correlated with emotional intelligence of the secondary school students.